REINTERPRETASI AYAT POLIGAMI PRESPEKTIF TEORI HERMENEUTIKA - Kemas Muhammad Gemilang (Institut Agama Islam Negeri Batusangkar, 2023)
The scholars argue that polygamy is part of the law which is permissible, although with conditions. However, according to Fazlur Rahman the implementation of polygamy can be abolished by understanding hermeneutics. But on the other hand, there are Islamic scientists/thinkers who argue against the use of hermeneutics in interpreting the Qur'an. So this research was carried out to look at the history and scope of hermeneutics along with opinions on the pros and cons, as well as applying this theory to the verses of the Al-Qur'an about polygamy. This research is a library research that relies on literature related to hermeneutics and Fazlur Rahman. The presentation of this research data is in the form of qualitative descriptive. The results of this research are that hermeneutics is a theory whose basis is used to interpret the Bible today, which has a different position from the Al-Qur'an, which still maintains its authenticity. Apart from that, it is feared that interpreters who use this theory will interpret the Al-Qur'an arbitrarily and feel that they understand the text better than the author or creator of the text. this is because there is no limit to the expertise that the interpreter must have. In his application of the verse about polygamy, Fazlur Rahman believes that current social conditions are not the same as previous social conditions. Currently, social conditions are more advanced and knowledgeable, both men and women. Social change is also supported by current technological advances which are also able to change people's understanding. So that the act of polygamy can be abolished and prohibited